Factors influencing intensive care unit length of stay after craniotomy for supratentorial tumor resection: an observational study - Abdelghafour El Koundi; Mehdi Samali; Meskine Amine; Khalil Mounir; Hicham Balkhi; Mustapha Bensghir (Journal of Neurocritical Care)
Background Few studies have explored the intensive care unit (ICU) requirements of patients after craniotomy. Identifying the factors that contribute to extended ICU stay can enhance ICU efficiency and reduce costs. This study investigated the predictors of prolonged ICU stay after craniotomy for supratentorial brain tumors to establish conditions enabling ICU bypass. Methods We retrospectively reviewed 205 patients admitted to the ICU after craniotomy for supratentorial brain tumors. Patients were categorized based on ICU length of stay (LOS): ≤24 hours (group 1) and >24 hours (group 2). Logistic regression analysis identified factors linked to extended ICU stay. Results Among the patients, 172 (84%) were discharged from the ICU within 24 hours, whereas 33 (16%) had longer stays. Independent predictors of prolonged ICU LOS included midline shift (odds ratio [OR], 2.494; 95% CI, 1.289–4.824; P=0.007), operative blood transfusion (OR, 1.295; 95% CI, 1.007–1.665; P=0.044), longer operative duration (OR, 1.027; 95% CI, 1.014–1.039; P<0.001), and new postoperative neurological deficits (OR, 1.865; 95% CI, 1.426–2.439; P<0.001). Conclusion These findings may optimize ICU resource allocation by identifying low-risk patients suitable for early transfer to the neuroscience floor. A selective ICU admission strategy can improve resource use, minimize costs, and enhance ICU availability.